Benzo[a]pyrene-mediated toxicity in primary pig bladder epithelial cells: A proteomic approach - Verma, Nisha; Pink, Mario; Rettenmeier, Albert W.; Schmitz-Spanke, Simone (Journal of Proteomics, 2013)
The studies described in this paper deal with a sequence of cellular events induced by the environmental toxicant benzo[a]pyrene (B[a]P) that were investigated in primary urinary bladder epithelia cells (PUBEC) from pigs by using a proteomic approach. Two-dimensional (2DE) gel electrophoresis unveiled the differences in protein expression between cells exposed to 0.5 extgreekmM B[a]P for 24 h and control cells. Twenty-five differentially expressed proteins involved in DNA repair, mitochondrial dysfunction, and apoptosis were identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). These findings were supported by the concentration-dependent increase in olive tail moments as determined by the comet assay and by a time-dependent increase in histone H2A.x (H2AX) phosphorylation upon B[a]P exposure. On the other hand, the expression of voltage-dependent anion channel 2 (VDAC2), cathepsin D (CTSD), heat shock protein 27 (HSP27), and heat shock protein 70 (HSP70) hinted to apoptosis occurring through the intrinsic apoptotic mitochondrial pathway. Taken together, these data suggest that B[a]P is capable of inducing DNA damage in urinary bladder epithelial cells at low concentrations during a short exposure period, thus eventually leading to cell death by apoptosis. Biological significance Epidemiological studies have indicated PAHs as potential candidates for initiating bladder cancer development, although the precise risk is still unknown (Kaufman et al. (2009) [1]). In recent years, the understanding of the metabolic capacity of urothelial cells has broadened continuously; i.e. a wide range of xenobiotic metabolizing cytochrome P450 enzymes (CYP) were detected in urothelial cells from humans and animals (Roos et al., 2006; Guhe et al., 1996 [2] and [3]), thus indicating that urothelial cells are not only passively exposed to reactive metabolites but also actively by intracellularly producing reactive intermediates that can induce cancer. Moreover, small quantities of non-metabolized B[a]P and its hydroxylated derivatives have been identified in blood and urine (Rossella et al. (2009) [4]). Thus, it appears plausible that B[a]P, a highly lipophilic compound, is taken up by the urothelium and metabolically activated to carcinogenic intermediates in these cells. In our previous studies with primary uroepithelial cells isolated from freshly slaughtered pigs we demonstrated the ability of these cells for a strong uptake of B[a]P and its conversion to the oxidative metabolite (3-OH–B[a]P) (Verma et al. (2012) [5]). The present study is a continuation of this previous work exhibiting the effects of B[a]P exposure on cellular functions of PUBEC. The results indicated caspase-dependent apoptosis induced by B[a]P due to DNA damage (possibly lethal double-strand breaks as indicated by H2AX phosphorylation). Taken together, these studies provide strong evidence for the ability of B[a]P to act as a bladder carcinogen.
EAM Import::2019-03-13